The reception of international law by constitutional courts through the prism of legitimacy - Niels Petersen (Max Planck Institute for Research on Collective Goods, 2009)
This contribution seeks to shed new light onto the classification of legal orders with respect to the domestic effect of international law. Traditional theory distinguishes between monist and dualist systems, those that accept the primacy of international law over domestic law, and those that do not attribute direct effect to international law in the domestic legal order. We will examine three different lines of constitutional jurisprudence on the effect of decisions of international authorities in the domestic order. It is maintained that all courts dealing with the domestic effect of international secondary law ultimately face questions of legitimacy of the external decisionmaking procedure. We will identify three strategies to cope with this challenge and argue that it is more appropriate to consider the relationship of a national legal order to international law through the prism of how its constitutional court approaches the governance issue than to refer to the traditional monism-dualism-dichotomy.
Keywords: 330